Effect on the concentration of glucose, cholesterol and triglycerides in albino rats fed with repeated doses (28 days) of honey in ethanol - Vílchez Cáceda, Héctor (2018)
Objective: To evaluate if the consumption of honey during 28 days produces variations in the concentrations of glucose, cholesterol and triglycerides in the Holtzman strain albino rats. Materials and methods: The study had an experimental, analytical, prospective and longitudinal design. A preliminary phytochemical screening of honey was carried out. For the biochemical study, forty (40) 14-week-old male Holtzman strain albino rats were used, which were randomized and divided into four groups of ten rats each: Group I (distilled water); Group II (10 % ethanol), Group III (2 % honey solution) and Group IV (2 % honey solution in 10% ethanol). All groups were fed p.o. for 4 weeks using an orogastric cannula. One additional week was assessed following the oral administration. Blood glucose, cholesterol and triglyceride concentrations were measured on days 0, 1, 7, 14, 21, 28 and 35. Results: The presence of alkaloids, triterpenoids and phenolic compounds was determined. In the biochemical study, Group IV presented an increase in the average body weight, and glucose and cholesterol concentrations; Group I showed an increase in the average concentration of triglycerides in blood serum. At the end of the study, Group IV presented a decrease in the average concentration of triglycerides. No alterations in the hematological parameters and leukocyte formula, or microscopic or macroscopic lesions related to the treatments under study were observed. Conclusions: Under experimental conditions, the consumption of 2 % honey in 10 % ethanol showed variations in blood glucose, cholesterol and triglycerides concentrations in albino rats.